ABI End of Initiative - 2024 Progress Deep Dive of the maize breeding teams from CIMMYT and IITA - Boddupalli, P. M. (International Maize and Wheat Improvement Center, 2024)
The presentation summarizes the maize breeding teams' efforts and progress from 2022 to 2024 through a series of questions that highlight the team's breeding achievements. It also discusses the team's successes and challenges during this period.